Betelvine (Piper betle L.): A potential source for oral care - Chowdhury, U.; Baruah, P.K. (Current Botany, 2020)
Piper betle L. (betelvine) is a valuable crop that is widely used as masticatory and with a long past history of varied traditional uses. Betelvine possesses numerous phytochemicals with important pharmacological attributes. Active molecules such as Fluoride, Eugenol, Hydroxylchavicol, Chlorogenic acid etc. present in betelvine with potent antibacterial, antifungal as well as anti-carcinogenic properties signify tremendous prospective of the plant for the formulation of natural product based drugs for maintaining hygiene and cure of diseases in the oral cavity.